Pemberdayaan Masyarakat Melalui Pelatihan Pakan Mandiri Ikan Nila Berbahan Baku Lokal - Sitti Fakhriyyah; Jalil Jalil; Irmawati Irmawati; Romi Setiawan; Ade Ikhlas Amal Alam; M. Irham Ilyas; Asmi Citra Malina; Andi Haerul; Husnaeni Husnaeni; Muh. Alwi; Syafruddin Syafruddin; Kusmaladewi Kusmaladewi; Syakira Permadani Machdi; Dian Purnamasari Anwar; Kamaruddin Kamaruddin (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
This community service activity aimed to enhance the capacity of tilapia farmers at the UPR Kampung Tengah, Gowa Regency, in producing locally based, self-formulated feed. The main problem faced by farmers was the high cost of commercial feed, which accounted for 60–70% of total production expenses. To address this issue, a training program was conducted consisting of socialization on tilapia nutritional requirements, selection of local feed ingredients (such as rice bran, fish meal, snail meal, and vitamin mix), and direct demonstrations of the pellet feed production process. The implementation methods included a pre-test, material presentation, post-test, and hands-on feed-making practice assisted by internship students. The results showed a significant improvement in participants’ understanding, with the average score increasing from 3.6 (pre-test) to 9.1 (post-test), indicating a gain of 5.5 points. Participants were also able to practice the feed processing stages, including grinding, mixing, molding, and drying. This training not only provided theoretical knowledge but also equipped farmers with practical skills in independent feed production, thereby reducing dependence on factory-made feed, lowering production costs, and promoting greater self-reliance and sustainability in tilapia aquaculture enterprises.